Multiple Deformation of Crystalline Rocks in the Tazin Group, Eldorado Fay Mine, NW Saskatchewan - Krupička, J.; Sassano, G. P. (Canadian Journal of Earth Sciences, 1972)
The crystalline rocks of the uranium-bearing Precambrian Tazin Group on the north shore of Lake Athabasca in Saskatchewan have long been known to contain a high proportion of cataclastic rocks. A detailed microscopic textural study of the Tazin rocks from the Eldorado Fay Mine, Beaverlodge, shows that: (a) all units of the Tazin Group have been affected by strong postcrystalline (partly syncrystalline) deformation; (b) in many places the deformation reached the highest degree of crushing encountered in sheared rocks; (c) deformation occurred in several distinct phases separated by considerable time intervals and at successively higher structural levels; and (d) the rocks are thus polydeformational.The deformation was so strong that many crystalline rocks have developed the outward appearance of argillites and tuffs.